Molecular dynamics simulation of graphene-based thin films for seawater desalination - Dahanayaka, Madhavi (Nanyang Technological University, 2020)
Since 71% of the earth’s surface is covered by the sea, seawater desalination plays a pivotal role in addressing the water crisis. Membrane separation technologies, including reverse osmosis, electrodialysis, forward osmosis, pervaporation and membrane capacitive deionization, have been the recent focus for many research studies because of their simplicity and relatively low energy cost in comparison to the thermal driven distillation processes. Nanotechnology has opened a window for researching new nanomaterials which enhance desalination performance in an economical and sustainable manner. Experimental synthesis of nanomaterials with optimized desalination performance is a trial and error process, requiring considerable resources and time. Molecular dynamics (MD) simulation is an efficient method in investigating the transport behaviours at the nanoscale and thus provides a powerful tool for the design and performance analysis of graphene (GE)-based thin films. This Ph.D. thesis research aims to investigate the seawater desalination performance in capacitive deionization, FO, electronanofiltration and PV systems by adopting four GE-based nanostructures, namely, corrugated GE layers, stacked GE sheets, ionized graphene oxide (GO) layers and GO/metal organic framework (MOF) nanocomposite, via MD simulation. The findings in this Ph.D. research advance the understanding of ion separation mechanisms through GE-based nanostructures and provide guidance on the experimental synthesis of GE-based thin films for seawater desalination.